Empowering Collaborative Learning Processes in Educational Institutes - Aguilar-González, Rita (2024)
This research article proposes to illustrate the advantages of the collaborative learning process that motivates the creation of harmonious environments in the educational environment. In this analysis the educational institute is considered as a company. For this reason, the traditional educational model known as “Master Class” where the professor gives an explanation, and the student takes notes or simply listens the class to acquire knowledge is obsolete. Nowadays the education is more participative where the students have a main role in the learning process. The students collaborate in the learning process sharing knowledge, ideas and information as they are part of a team work. Moreover, leadership types such as the methodology of accompanying leadership which helps professors in their daily labors in aspects such as. Situational leadership, Empowerment, role games, shared vision and work tools. Finally, the results illustrate the advantages of the collaborative learning process which motivates the creation of harmonic environments in the educational environment.